2007
DOI: 10.1016/j.nurt.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Seletracetam (UCB 44212)

Abstract: Summary:Better pharmacotherapies for epilepsy are needed for patients who are refractory to or have tolerability difficulties with current treatments. Seletracetam, a new drug in epilepsy development, is a pyrrolidone derivative structurally related to levetiracetam (trade name Keppra). It was discovered because of its high binding affinity to the synaptic vesicle 2A (SV2A) protein, which is now known to be the binding site for this family of compounds. Seletracetam shows very potent seizure suppression in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In our previous study, synaptotagmin I was up-regulated in temporal lobe tissues of patients with IE (Xiao et al 2009). The observation that SV2A knockout mice develop lethal seizures soon after birth (Crowder et al 1999), along with evidence that SV2A is the binding site for the AED levetiracetam and its analogs (brivaracetam and seletracetam; Lynch et al 2004;Gillard et al 2006;Bennett et al 2007;von Rosenstiel 2007), indicates a role for SV2A in the antiepileptic properties of AEDs. Therefore, decreased SV2A expression may contribute to the progression of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, synaptotagmin I was up-regulated in temporal lobe tissues of patients with IE (Xiao et al 2009). The observation that SV2A knockout mice develop lethal seizures soon after birth (Crowder et al 1999), along with evidence that SV2A is the binding site for the AED levetiracetam and its analogs (brivaracetam and seletracetam; Lynch et al 2004;Gillard et al 2006;Bennett et al 2007;von Rosenstiel 2007), indicates a role for SV2A in the antiepileptic properties of AEDs. Therefore, decreased SV2A expression may contribute to the progression of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is synaptic vesicle protein 2 (SV2), a membrane glycoprotein expressed exclusively in neurons and endocrine cells. SV2 is the binding site of a class of drugs typified by levetiracetam (5,17,26,29,31). Levetiracetam is a Food and Drug Administration-approved treatment for epilepsy (reviewed in Ref.…”
mentioning
confidence: 99%
“…Apart from various similarities seletracetam differs from levetiracetam by a very potent and selective effect against Zn concentrations involving multiple high-voltage-operated Ca 2+ channels. In pharmacokinetic studies seletracetam was found to reach C max within 1 h. The linear, timeindependent pharmacokinetics of the drug combined with a rapid and almost complete absorption indicates that STM has a major uncomplicated pharmacokinetic profi le (60).…”
Section: Antiepileptic Drugs (Structures See Figure 2)mentioning
confidence: 95%